Modeling Students' Mathematical Modeling Competencies ICTMA 13 - Lesh, Richard; Galbraith, Peter L.; Haines, Christopher R.; Hurford, Andrew; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
As we enter the 21st century, there is an urgent need for new approaches to mathematics education emphasizing its relevance in young learners$1 (Bfutures. Modeling Students$1 (BMathematical Modeling Competencies explores the vital trend toward using real-world problems as a basis for teaching mathematics skills, competencies, and applications. Blending theoretical constructs and practical considerations, the book presents papers from the latest conference of the ICTMA, beginning with the basics (Why are models necessary? Where can we find them?) and moving through intricate concepts of how students perceive math, how instructors teach$1 (Band how both can become better learners. Dispatches as varied as classroom case studies, analyses of math in engineering work, and an in-depth review of modeling-based curricula in the Netherlands illustrate modeling activities on the job, methods of overcoming math resistance, and the movement toward replicable models and lifelong engagement. A sampling of topics covered: How students recognize the usefulness of mathematics Creating the modeling-oriented classroom Assessing and evaluating students$1 (Bmodeling capabilities The relationship between modeling and problem-solving Instructor methods for developing their own models of modeling New technologies for modeling in the classroom Modeling Students$1 (BMathematical Modeling Competencies offers welcome clarity and focus to the international research and professional community in mathematics, science, and engineering education, as well as those involved in the sciences of teaching and learning these subjects.s
Modeling and Design Research and Assessment Methodologies -- Modeling in High School and College -- Modeling in Middle Schools -- Modeling in the Primary Grades -- Modeling and Teacher Development -- Modeling vs. Traditional Problem Solving -- Modeling in Engineering and in Other 21st Century Design Sciences -- Technological Tools and Data Modeling -- Modeling and Socio-Cultural Perspectives -- Directions for the Future.
Keywords: Education; Mathematics; Education; Mathematics Education; Mathematical Modeling and Industrial Mathematics